The Use of Information Management as a Decision Making Tools of Prophet Sulaiman - Anang Kunaefi; Nita Yalina (Systemic: Information System and Informatics Journal, 2016)
In the information era today, value of data and Information is increasing rapidly. Data and information become more and more important to organization, because it is used as a tools in making decisions. A lot of concept and theory about data and information management has been launched. Our research tried to study and make a bridge between today’s theory about information management and Islamic values based on Islamic history written in Alquran. We took Prophet Sulaiman as our case. Sulaiman was a Prophet as well as a King. He was awarded intelligence and wisdom of God. We learn the story of Sulaiman and performed a literature review and cross references to various theories of information management. We found that Prophet Sulaiman uses data and process it into valuable information, to make right decision. We believe that, during his age, Prophet Sulaiman had implement basics of information management concept and theory.